Chlamydial Pneumonitis: A Creepy Neonatal Disease. (12th February 2013) - Hon, Kam Lun; Leung, Alexander K. C.
Abstract : We present a case of neonatal chlamydial pneumonitis to illustrate that a high index of suspicion is necessary to make the diagnosis so that treatment can be promptly instituted. The child was afebrile and the only symptom was a cough. The respiratory equations are calculated to understand the respiratory physiology. There was no overt abnormality with ventilation, oxygenation, compliance, resistance, or ventilation-perfusion mismatch despite radiographic abnormality. The literature is searched to review if treatment with a systemic macrolide antibiotic is needed in an otherwise asymptomatic neonate with chlamydial pneumonitis.